2012
DOI: 10.1089/aid.2011.0122
|View full text |Cite
|
Sign up to set email alerts
|

HIV Type 1 Genetic Diversity and Naturally Occurring Polymorphisms in HIV Type 1 Kenyan Isolates: Implications for Integrase Inhibitors

Abstract: Little is known about the extent and predictors of polymorphisms potentially influencing susceptibility to HIV integrase inhibitors. HIV-1 genetic diversity and drug resistance are major challenges in patient management globally. To evaluate HIV genetic diversity and drug resistance-associated mutations within a Nairobi cohort, genetic analysis of the HIV-1 pol-integrase gene regions was performed on samples collected from 42 subjects and 113 Kenyan intergrase sequences deposited in the Los Alamos HIV database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…The fact that only 0.6% of samples analyzed had INSTIs major RAMs suggests that there will be a lesser likelihood of resistance to INSTIs in Cameroon and that INSTIs will be effective for HIV-infected Cameroonians. Similar trends were observed in other countries in Africa [13,34,[43][44][45], Asia [46][47][48][49][50][51], Europe [52][53][54], and South America [55] where studies showed a low frequency of INSTIs major RAMs.…”
Section: Discussionsupporting
confidence: 81%
“…The fact that only 0.6% of samples analyzed had INSTIs major RAMs suggests that there will be a lesser likelihood of resistance to INSTIs in Cameroon and that INSTIs will be effective for HIV-infected Cameroonians. Similar trends were observed in other countries in Africa [13,34,[43][44][45], Asia [46][47][48][49][50][51], Europe [52][53][54], and South America [55] where studies showed a low frequency of INSTIs major RAMs.…”
Section: Discussionsupporting
confidence: 81%
“…Demographic data such as age and gender, together with any history of any other disease other than HIV, were also obtained using a self-reporting questionnaire. Collected samples were tested for HIV-1 antibodies using a rapid detection kit (Determine HIV-1/2, Abbott, Japan) and Bioline HIV-1/2, Republic of Korea [23]. …”
Section: Methodsmentioning
confidence: 99%
“…The cycling conditions for this PCR were similar, that is, one cycle at 94°C for 5 min followed by 35 cycles each of 94°C for 1 min, 62°C for 1 min, and 72°C for 1 min with a final extension step which will be carried out at 72°C for 5 min [25]. The PCR amplification was confirmed by visualization with ethidium bromide staining of the agarose gel [23]. …”
Section: Methodsmentioning
confidence: 99%
“…A n important feature of the HIV-1 genome is its extraordinary variability, which is among the main factors allowing the virus to evade selective pressure from the immune system, vaccines, and therapies. 1,2 Exhibition of tremendous genetic variation in HIV-1 due to its high mutation rates and recombination 2,3 has led to classification of the virus into four distantly related phylogenetic groups of HIV-1: Main group (M), Outlier group (O), and non-M-non-O group (N) and group P. 3 Group M is further subdivided into at least 12 distinct lineages, designated as subtypes and subsubtypes (A1, A2, B, C, D, F1, F2, G, H, J, K, and L) and 48 circulating recombinant forms (CRF). 2,3 HIV-1 genetic variants are unevenly disseminated in different geographic locations.…”
mentioning
confidence: 99%
“…1,2 Exhibition of tremendous genetic variation in HIV-1 due to its high mutation rates and recombination 2,3 has led to classification of the virus into four distantly related phylogenetic groups of HIV-1: Main group (M), Outlier group (O), and non-M-non-O group (N) and group P. 3 Group M is further subdivided into at least 12 distinct lineages, designated as subtypes and subsubtypes (A1, A2, B, C, D, F1, F2, G, H, J, K, and L) and 48 circulating recombinant forms (CRF). 2,3 HIV-1 genetic variants are unevenly disseminated in different geographic locations. 4 It has been found that from the beginning of the epidemic, distribution of different genetic variants has been changing due to population movements and the emergence of new recombinant forms.…”
mentioning
confidence: 99%